Brand Image and Product Quality on The Decision to Purchase Cooking Oil in Semarang City Through Price as A Mediating Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the influence of brand image and product quality on consumer purchasing decisions for cooking oil, with consumer satisfaction as a mediating variable. The research method used is quantitative descriptive, with primary data collected through questionnaires. The sampling technique used non-probability sampling using purposive sampling. The sample in this study was 150 respondents. The data analysis technique used Partial Least Square (PLS) with SmarthPLS version 3 software. The results of the study are: Product quality has no influence on purchasing decisions for cooking oil. Price has a positive and significant effect on purchasing decisions for cooking oil. Product quality has a positive and significant effect on consumer satisfaction for cooking oil. Price has a positive and significant effect on purchasing decisions for cooking oil. Brand image has a positive and significant effect on purchasing decisions. Brand image mediates product quality and purchasing decisions for cooking oil. Consumer satisfaction mediates price and purchasing decisions for cooking oil.
Keywords: Product quality; price, brand image; purchasing decisions